Optimalisasi Konten Edukasi Islam Berbasis Short Video sebagai Media Dakwah dan Pembelajaran di Era Digital - Wandi W; Rosdialena R (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The growth of digital technology has fundamentally changed the ways people communicate, learn, and share religious information in society. Short video platforms like TikTok, Instagram Reels, and YouTube Shorts are increasingly taking over how young people access knowledge, including Islamic knowledge. This phenomenon brings both opportunities and challenges for carrying out Islamic preaching and learning in a way that is effective and responsible. This article aims to analyze the potential of optimizing short video content focused on Islamic education as a means of preaching and learning in the digital age. It uses a conceptual paper approach based on literature review. The research used a literature review method by analyzing various national and international scientific sources that discuss digital preaching, Islamic learning media, digital literacy, and the use of short video platforms. The study’s results show that short videos are very effective in capturing the audience’s attention, boosting engagement, and spreading the values of Islam to a wider audience. However, there are serious challenges such as the risk of oversimplifying religious material, spreading unverified information, the dominance of platform algorithms, and low levels of religious digital literacy. This article presents an integrated conceptual model as a framework for developing Islamic preaching and learning through short videos that are adaptable, educational, and sustainable.